Evaluation of Teaching Techniques for Introductory Accounting Courses - Vruwink, David R.; Otto, Janon R. (The Accounting Review, 1987)
[This study tests the effect of homework collection and quizzes on exam scores. Expectancy theory as modified by Porter and Lawler [1968] suggests that performance (a student's exam score) is dependent upon effort, abilities and traits, and role perception (regarding the class). An accounting instructor is able to influence a student's effort through assigning different tasks (teaching techniques) which may include homework collection or quizzes. In this study, a Latin square design allows several teaching techniques to be tested in four accounting classes and controls for possible bias in exam scores resulting from time of class and exam difficulty. Additionally, GPA is used as a covariate. The results indicate that the selected teaching techniques do not significantly affect exam scores.]